Assessing reading - Alderson, J. Charles (Cambridge University Press, 2005)
Includes bibliographical references (p. 358-376) and index; This is a comprehensive and up-to-date treatment of the assessment of reading in a foreign or second language. It reviews theory, research and practice in the assessment of reading; First published 2000